2017
DOI: 10.3847/1538-4357/aa8a6e
|View full text |Cite
|
Sign up to set email alerts
|

Stripped Elliptical Galaxies as Probes of ICM Physics. III. Deep Chandra Observations of NGC 4552: Measuring the Viscosity of the Intracluster Medium

Abstract: We present results from a deep (200 ks) Chandra observation of the early-type galaxy NGC 4552 (M89) which is falling into the Virgo cluster. Previous shallower X-ray observations of this galaxy showed a remnant gas core, a tail to the South of the galaxy, and twin 'horns' attached to the northern edge of the gas core (Machacek et al. 2005a). In our deeper data, we detect a diffuse, low surface brightness extension to the previously known tail, and measure the temperature structure within the tail. We combine t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…Indeed, nearby clusters have shown that ram pressure stripping could lead to tails of cool (≈0.5-1.0 keV) X-ray gas trailing behind galaxies, but such X-ray tails have typical 0.5-2.0 keV X-ray luminosities of ≈10 40 erg s −1 . This is 4 orders of magnitude smaller than what is expected for a cool core in a massive cluster-and would be undetectable with 170 ks of Chandra observations at the redshift of SpARCS1049 (e.g., Sun et al 2010;Zhang et al 2013;Kraft et al 2017). The brightest ram pressure stripped X-ray tail discovered to date has a 0.5-2.0 keV X-ray luminosity of 10 42 erg s −1 (e.g., Schellenberger & Reiprich 2015), which remains too faint to be significantly detected with Chandra in 170 ks at the redshift of SpARCS1049.…”
Section: Runaway Gas Cooling As the Source Of The Starburstmentioning
confidence: 72%
“…Indeed, nearby clusters have shown that ram pressure stripping could lead to tails of cool (≈0.5-1.0 keV) X-ray gas trailing behind galaxies, but such X-ray tails have typical 0.5-2.0 keV X-ray luminosities of ≈10 40 erg s −1 . This is 4 orders of magnitude smaller than what is expected for a cool core in a massive cluster-and would be undetectable with 170 ks of Chandra observations at the redshift of SpARCS1049 (e.g., Sun et al 2010;Zhang et al 2013;Kraft et al 2017). The brightest ram pressure stripped X-ray tail discovered to date has a 0.5-2.0 keV X-ray luminosity of 10 42 erg s −1 (e.g., Schellenberger & Reiprich 2015), which remains too faint to be significantly detected with Chandra in 170 ks at the redshift of SpARCS1049.…”
Section: Runaway Gas Cooling As the Source Of The Starburstmentioning
confidence: 72%
“…Several external processes have been proposed to explain the quenching of star-forming galaxies as they become satellites. Examples include ram-pressure stripping (Gunn & Gott 1972;McCarthy et al 2008), thermal evaporation (Cowie & Songaila 1977;Nipoti & Binney 2007), and viscous stripping (Nulsen 1982;Kraft et al 2017), all of which invoke the removal of the cold interstellar medium of a galaxy via its hydrodynamical interaction with the hot intergalactic medium of high-density environments as the reason for quenching. These processes are correlated with the velocity of a galaxy as it travels through its environment, and generally quench galaxies quickly.…”
Section: Satellite Quenching At Low Redshiftsmentioning
confidence: 99%
“…In Figure 5, we present the XMM-Newton surface brightness profile of M49 in the 0.7-1.3 keV energy band to the north. The energy band was chosen to maximize the source-to-background ratio (Ettori et al 2010;Kraft et al 2017). The previously reported bright edge (Irwin & Sarazin 1996;Biller et al 2004;Kraft et al 2011) is visible at ∼ 20 kpc north of the group center (marked by the magenta solid line).…”
Section: Surface Brightness and Contact Discontinuitymentioning
confidence: 99%